Efekitvitas Layanan Konseling Kelompok dengan Pendekatan Realita untuk Mengatasi Kesulitankomunikasi Interpersonal Peserta Didik Kelas X MAN Krui Lampung Barat T.P 2015/2016 - El Fiah, Rifda; Anggralisa, Ice (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2015)
Interpersonal communication possessed by students is far from the expectations of teachers. For example, to talk with friends, students are more busy with personal matters. One effort to overcome the problem of communication difficulties is through group counseling services with a reality approach. This study aims to determine whether or not the effective use of group counseling services with a reality approach to overcome the interpersonal communication difficulties of Class X MAN Krui 1 Lampung Barat students in the 2015/2015 academic year. The research design is a one-group pretest-posttest design experimental research. The population of this research is all students of MAN Krui, West Lampung. The research sample uses a purposive sampling approach / sample aims to obtain the number of samples in this study as many as 10 students. There are two research variables used, namely group counseling services with a reality approach as an independent variable, which is symbolized by (X) and interpersonal communication as a dependent variable symbolized by (Y). The instrument in data collection in this study uses a questionnaire and supporting methods in the form of observation . Validity test is done through the Z test shown by changes in students' interpersonal communication scores from the pre-test results of 95 and post-test results of 143.4 then there is a difference of 48.4. Group counseling services with an effective reality approach to overcome students' interpersonal communication difficulties, it can be seen from the hypothesis testing that the calculation results are Zhitung = 2.803> Ztable = 1.96 from a significant 0.05% and degrees of freedom (db = n - 2 = 10 - 2 = 8)